Broadband microwave absorption and improved electromagnetic performance of iron oxide–activated carbon hybrid composites in the Ku-band - Bello, Murtala Alhaji; Azis, Raba'ah Syahidah; Yusmadi, Nurul Asiya Nadhirah; Ismail, Ismayadi; Shabdin, Muhammad Kashfi; Osman, Nurul Huda; Yakubu, Abubakar; Sani, Yusuf (Elsevier B.V., 2025)
This study explores the enhancement of microwave absorption properties in iron oxide (IO) composites through the incorporation of bio-waste-derived activated carbon (AC). Composite materials were synthesized using a cost-effective ball-milling method, combining commercially sourced activated carbon and iron oxide. The addition of highly conductive activated carbon to the ferrite matrix significantly improved reflection loss due to enhanced interfacial polarization. The dielectric permittivity and dielectric loss tangent of IO also increased with the introduction of AC. To evaluate their microwave absorption performance, the composites were embedded in epoxy resin and fabricated into single-layer structures with a 2 mm thickness. The IO/AC hybrid composite demonstrated exceptional microwave absorption, exceeding 99.9 % efficiency, with a minimum reflection loss of −39.09 dB and an absorption bandwidth of 5.28 GHz in the Ku-band region. This research introduces the novel application of bio-waste-derived activated carbon for enhancing the microwave absorption efficiency of iron oxide. The findings highlight a sustainable and cost-effective approach for developing high-performance electromagnetic wave absorbers, contributing to waste reduction and environmental sustainability.